Culicidae (Diptera: Culicomorpha) in the southern Brazilian ‘Ana Leuch Lozovei’ collection, with notes on distribution and diversity - Maurício dos Santos Conceição; Samira Chahad-Ehlers; Luiz Gonzaga dos Santos-Neto; Adson Luís Sant’Ana; Gabriela Princival Marques Ribeiro; Débora do Rocio Klisiowicz; Cássio Lázaro Silva-Inacio; Taciano de Moura Barbosa; Renata Antonaci Gama; Ana Leuch Lozovei; Andrey José de Andrade (GigaByte)
Biological collections are important for acquiring knowledge of the biodiversity of a specific environment. Here, we organize, list and catalog adult specimens of Culicidae from the Parasitology Collection of the Basic Pathology Department at the Federal University of Paraná, Brazil, and present a databank of taxonomic and collection information for each sample. Culicids were collected using different methodologies in 18 municipalities in Paraná state, between 1967 and 1999. There are 5,739 catalogued specimens, of which 4,703 (81.94%) are identified at species level, with a diversity of 100 species. Of these, 18 are new recorded samples for Paraná, and three are new for Brazil. This collection is named the Ana Leuch Lozovei Entomological Collection in honor of the 30 years Prof Lovozei dedicated to culicid study in Paraná. The collection comprises insect vectors or potential vectors, of agents causing human diseases.